Glycosylation on the Antifreeze and Antioxidant Capacities of Tilapia Gelatin Hydrolysates - Ying Liu; Zongcai Tu; Qiuyu Lu; Shengnan Zhan; Ru Jia; Zhaohui Qiao; Huamao Wei; Tao Huang (Fishes)
The antifreeze and antioxidant capacities of tilapia (Oreochromis mossambicus) gelatin hydrolysates were investigated, after glycosylation with saccharides of varying molecular weights, to enhance their functional properties to widen its commercial application in frozen aquatic products. Glycosylation was conducted by mixing gelatin hydrolysates with ribose, glucose, maltose, and dextran (20 kDa) at a 1:1 mass ratio; the glycosylation products had a pH of 10 and were incubated at 80 °C for 1 h. The results showed that the glycosylation degree ranked as: ribose > glucose > maltose > dextran. The mass spectrometry analysis showed that 17, 32, and 5 glycosylation sites were identified for ribose, glucose, and maltose, respectively, suggesting a molecular weight-dependent effect. Spectroscopic analyses, including ultraviolet and infrared spectroscopy, revealed that the gelatin hydrolysate structure was expanded, with chromophores in hydrophilic environments; a blue shift in the amide A and II bands confirmed that the amino group was involved. Fluorescence spectroscopy showed conformational changes with a red shift at 303.4 nm and a reduction in intensity. Antifreeze activity, such as catalase freezing protection and shrimp surimi protein stability, and antioxidant activity, including radical scavenging and metal ion chelation, were significantly improved. Ribose exhibited the strongest effects, followed by maltose and glucose. These results demonstrate the potential of glycosylation to improve gelatin hydrolysates for functional applications.